2007
DOI: 10.1038/nm1554
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ mediates CD4+ T-cell loss and impairs secondary antitumor responses after successful initial immunotherapy

Abstract: Protective cell-mediated immune responses in cancer are critically dependent on T-helper type 1 (T(H)1) cytokines such as interferon-gamma (IFN-gamma). We have previously shown that the combination of CD40 stimulation and interleukin-2 (IL-2) leads to synergistic antitumor responses in several models of advanced metastatic disease. We now report that after this treatment and other immunotherapy regimens, the CD4+ T-cell population, in contrast to CD8+ T cells, did not significantly increase but rather exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 24 publications
11
128
1
1
Order By: Relevance
“…These downstream effects are critical to the development of cellular and humoral immune responses; 16 however, sole CD40 stimulation in murine melanoma vaccine studies has impaired development of durable tumor responses. 17 Our findings with CD86 are similar to others showing diminished expression of this marker in peripheral blood monocytes of patients with melanoma. 18 Diminished expression of CD40 and CD86 has been found in sentinel lymph nodes without metastasis when compared with nonsentinel lymph nodes without metastasis in melanoma 19 and breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…These downstream effects are critical to the development of cellular and humoral immune responses; 16 however, sole CD40 stimulation in murine melanoma vaccine studies has impaired development of durable tumor responses. 17 Our findings with CD86 are similar to others showing diminished expression of this marker in peripheral blood monocytes of patients with melanoma. 18 Diminished expression of CD40 and CD86 has been found in sentinel lymph nodes without metastasis when compared with nonsentinel lymph nodes without metastasis in melanoma 19 and breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…CD4 ϩ T cells are not the only source of IL-2 that provides help for the primary T cell response according to a recent study (49), but for the memory response this remains to be examined. A role for CD27-regulated IFN-␥ production seems less likely, since IFN-␥ was recently shown to impair, rather than enhance, secondary responses of CD8 ϩ T cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with this concept, other studies have found that IFN-g enhances activation-induced cell death and that this cytokine might regulate the expansion and persistence of effector T cells (Teff) by enhancing intrinsic and extrinsic pathway-dependent apoptosis [22,23]. Thus, although IFN-g is a crucial effector cytokine in the primary immune response, it can occasionally lead to apoptosis of CD4 1 T cells that are critical for the memory immune response [24]. (Fig.…”
Section: Introductionmentioning
confidence: 91%